Kualitas Pelayanan Pengaduan Kasus Kekerasan Anak Di Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Palu - Pratama, Putra; Intan, Intan; Manda, Manda; Amalia, Rezki; Diva, Diva; Mustainah, Mustainah; Kurnia, Intam; Haryono, Dandan (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
This study aims to analyze the quality of complaint services for child abuse cases at the Office of Women’s Empowerment and Child Protection (DP3A) of Palu City in supporting child protection efforts. The study focuses on five dimensions of service quality: responsiveness, assurance, tangibles, empathy, and reliability. This research employs a descriptive qualitative approach. Data collection techniques include in-depth interviews, observations, and documentation. The informants in this study consisted of the Head of the Child Abuse Division, service staff, and data operators, who are directly involved in the process of receiving and handling complaints. Data analysis was conducted through data condensation, data display, and conclusion drawing. The findings reveal that the dimensions of responsiveness, assurance, tangibles, and empathy have been implemented quite effectively. Officers are able to provide initial responses, explain service procedures, and demonstrate concern for complainants and victims. Facilities such as service rooms and counseling rooms are available, although improvements in comfort are still needed. However, reliability has not been optimal due to delays in case follow-up, inconsistent progress information, and cross-sector coordination barriers, which reduce public trust. The study concludes that the quality of complaint services for child abuse cases at DP3A Palu City is not yet optimal.